Cytological changes during certain reproductive conditions in in-vitro uterine flushing in buffaloes (Bubalus bubalis) - PROMOD, K; MAHMOOD, S; SINGH, R (The Indian Journal of Animal Reproduction, 2023)
Cytological changes during follicular, luteal phase, inactive ovarian stage and infected uterine flushingsin-vitro were studied in buffalo uteri (n-54) collected from local abattoir. The overall total nucleated and epithelialcell count was significantly (P
Keywords: Buffalo; uterus; cell cytology